ВИМІРЮВАЛЬНИЙ КАНАЛ ВІБРОЗМІЩЕННЯ З ЄМНІСНИМ СЕНСОРОМ - Осельський, О. В.; Кухарчук, В. В. (Вісник Вінницького політехнічного інституту, 2025)
The article considers the importance of using vibration monitoring as an effective means of diagnosing the condition of electromechanical systems and complexes in a production environment. The features that arise during monitoring of electromechanical systems operating at low speeds are presented, namely, low vibration frequency, weak signal amplitude and the influence of external noise. The significant disadvantages of low-frequency vibration displacement sensors are analyzed, among which it is worth noting — low reliability and low accuracy in the infra-low frequency band, installation complexity, high cost. The use of accelerometers, the main measurement parameter of which is vibration acceleration, leads to significant errors. Since vibration displacement is the most effective vibration measurement parameter for machines with low rotational speed, this paper considers the use of a capacitive sensor for measuring vibration displacement conversion into a time interval as the main measurement tool. The conversion equation, structural diagram and timing diagrams of its operation are shown. Microprocessor circuit of a vibration displacement measuring channel with a capacitive sensor of time-pulse conversion, operating under the control of a microcontroller, is proposed. The principle of operation of a digital vibration displacement measuring channel in binary code is described, the conversion equation is given. The static characteristics (graphical representation of the conversion equation) of this vibration displacement measuring channel (in the range: a = 20·10–6…120·10–6 m) with a capacitive sensor are estimated. Since as a result of quantization of the analog value of the time interval tа, which has an infinite number of values, is replaced by a limited number of pulses N (periods) T0, such a metrological procedure leads to the appearance of a quantization error. Therefore, the equation of the relative quantization error for a vibration displacement measuring device with a capacitive sensor and the graphical dependence of the change in the relative quantization error on the measured vibration displacement value are given. It was established that at small values of vibration displacement the quantization error is small, at large values — this error increases. Based on the theory of measurement information, the choice of the bitness n of the binary counter is justified, which allows at the stage of developing the technical task to estimate the lower limit of measurement. It was established that the upper limit of measurement of the upper limit of vibration displacement measurement is limited by the normalized value of the quantization error, and the lower limit — by the bitness of the binary counter. The corresponding graphical dependencies are presented.